Characterization of parameters and strategies used by physical therapists in difficult mechanical ventilation weaning - Fabíola Maria Sabino Meireles; Isabel Oliveira Barbosa; Márcia Cardinalle Correia Viana; Cymara Pessoa Kuehner (Universidade de Fortaleza, 2013)
Objective: To characterize the main strategies and parameters used by physical therapists in difficult mechanical ventilation weaning. Methods: Cross-sectional study including all the physical therapists working in adult Intensive Care Units in three public hospitalsin Fortaleza-CE. A questionnaire with closed questions related to difficult mechanical ventilation weaning was applied, with either one or multiple answers. The data was treated with descriptive and non-parametric analysis. Results: Among the parameters mostly used by the 56 interviewed physical therapists for the difficult weaning, were found: current volume reduction (26 - 46.4%) and desaturation during aspiration (17 - 30.4%). It was observed that 38 (67.9%) alternate T-tube and continuous positive airway pressure (CPAP) as strategies for difficult weaning, and 28 (50%) reported reducing the pressure support. There was no statistical difference between the strategies used in the studied hospitals, neither correlation between strategies and parameters. Conclusion: It was found that physical therapists have been performing similar strategies, which are also shown in the literature, but this is not the case with the parameters. The parameters used are not supported by the literature.